2022
DOI: 10.3389/fmed.2022.891369
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Clinical Application of Innovative Optical Ophthalmic Imaging Techniques

Abstract: The field of ophthalmic imaging has grown substantially over the last years. Massive improvements in image processing and computer hardware have allowed the emergence of multiple imaging techniques of the eye that can transform patient care. The purpose of this review is to describe the most recent advances in eye imaging and explain how new technologies and imaging methods can be utilized in a clinical setting. The introduction of optical coherence tomography (OCT) was a revolution in eye imaging and has sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 503 publications
0
4
0
Order By: Relevance
“…(70)(71)(72)(73)(74) From the literature, it is observed that a few researchers have carried out a review on smartphone-based retinal image analysis concluding that it is a quick and cost-effective tool. (75)(76)(77)(78) Further supportive data for this notion were obtained by Malerbi et al (79) in the retrospective study that evaluated the capability of semiautomated DR screening with mobile handheld retinal camera to diagnose mtm-DR and VTDR after pupil dilation in 824 patients. It has been reported that the system achieved 97.8% sensitivity and 61.4% specificity, maintaining a sufficient quality of images in more than 80% of the cases.…”
Section: Discussionmentioning
confidence: 73%
“…(70)(71)(72)(73)(74) From the literature, it is observed that a few researchers have carried out a review on smartphone-based retinal image analysis concluding that it is a quick and cost-effective tool. (75)(76)(77)(78) Further supportive data for this notion were obtained by Malerbi et al (79) in the retrospective study that evaluated the capability of semiautomated DR screening with mobile handheld retinal camera to diagnose mtm-DR and VTDR after pupil dilation in 824 patients. It has been reported that the system achieved 97.8% sensitivity and 61.4% specificity, maintaining a sufficient quality of images in more than 80% of the cases.…”
Section: Discussionmentioning
confidence: 73%
“…Although ERM cell population deserves more investigation, our finding about ROS, iNOS, VEGF, Ang-2, NRF2, and NOX4 expression in ERMs and vitreal fluids might represent a key aspect in the developing of individualized therapies [64]. Noteworthy, ERM can slowly progress and deepen the effects on the whole macula, and the risk of developing ERMs rises with ageing and genetic/epigenetic predisposition (ocular and systemic assets) [65]. In this context, it would be of interest to highlight that the entity of inflammation at early stages (at stage 3) might be the explanation of the increased p65NFkB mRNA expression, as confirmed by the reduced inflammation and the absence of p65NFkB mRNA expression at stage 4.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mild nature of the symptoms, patients might suffer multiple episodes of ocular hypertension and therefore develop optic nerve damage before presenting to a specialist. In recent years, technology has developed that makes high-resolution retinal imaging possible, and several papers have suggested the importance of evaluating the retinal layer thickness to better understand the physiopathology of ocular, neurological or systemic diseases ( 19 , 20 ). In an effort to provide a more sensible tool for detecting early glaucomatous change, we used the mGCIPL thickness and found that the PSS-affected eyes exhibited a significant decrease on average and in all quadrants compared with the PSS-fellow eyes, indicating the death of a great number of RGC and loss of their axons.…”
Section: Discussionmentioning
confidence: 99%